Occupational Burnout as a Consequence of Workaholism – An Outline of the Problem Based on Studies of Polish Women Running Their Own Business Activity - Dobrowolska, Małgorzata; Paruzel-Czachura, Mariola; Chudzicka-Czupala, Agata; Stasila-Sierdzka, Marta; Siwiorek, Janusz (European Journal of Economics and Business Studies, 2018)
The paper presents selected studies using structured in-depth psychological interviews conducted in 2017 among n=72 women undergoing therapy for managers, who complained about ailments related to workaholism and simultaneous occupational burnout. The sample was selected by quota sampling, and running one’s own business was the criterion. The characteristic problem areas declared by the patients were divided into twelve categories, in accordance with the literature presented and with results of research conducted so far into workaholism and occupational burnout. The authors believe that occupational burnout is the principal consequence of workaholism, and the most serious one affecting occupational activity
Keywords: occupational burnout, workaholism, women, female entrepreneurs, qualitative research